Comparative Economic Competitiveness Analysis of Soybean Farming with and without Subsidy to Rice and Corn Farming in Bancak Sub-district, Semarang - Febyningsi Rambu Ladu Mbana; Tinjung Mary Prihtanti; Yuliawati Yuliawati (Agriekonomika, 2020)
In Indonesia, soybeans are categorized as secondary crops with high demand. Indonesian government still emphasizes soybean self-sufficiency and efforts to grow soybean production, but the low yields and limited profitability of soybeans imply that Indonesian farmers will continue to grow other crops, namely rice or corn. This study aims to identify whether the Semarang district government must issue  seed subsidies to support soybean competitiveness in terms of productivity and minimum prices so that it can compete with other crops, namely rice, and corn. Primary and secondary data are used in this study. Primary data were collected in a field survey in Bancak District. The sampling method uses a purposive sampling technique, which interviewed 45 farmers. Analyzed using descriptive statistics and competitiveness matrix analysis. The results showed that the analysis of soybean competitiveness was lower than rice and corn despite the existence of subsidy assistance.